2010
DOI: 10.1007/s10535-010-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of heat shock protein gene hsp26 in Arabidopsis thaliana enhances heat tolerance

Abstract: In the yeast Saccharomyces cerevisiae, the molecular chaperone HSP26 has the remarkable ability to sense increases in temperature directly and can switch from an inactive to a chaperone-active state. In this report, we analyzed the effect of expression of HSP26 in Arabidopsis thaliana plants and their response to high temperature stress. The hsp26 transgenic plants exhibited stronger growth than wild type plants at 45 °C for 16 h. The chlorophyll content and chlorophyll fluorescence decreased much more in wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Previous studies have revealed that heat stress was accompanied by growth suppression (Vierling 1991, Xue et al 2010. Our data showed that growth rate was more reduced in SR callus than that in DR callus, suggesting that DR callus was more resistant to growth suppression imposed by heat stress than SR callus (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies have revealed that heat stress was accompanied by growth suppression (Vierling 1991, Xue et al 2010. Our data showed that growth rate was more reduced in SR callus than that in DR callus, suggesting that DR callus was more resistant to growth suppression imposed by heat stress than SR callus (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…2B). Moreover, it has been reported that heat stress induced oxidative stress in plant, which resulted in cellular membrane injuries, solute and electrolyte leakage (Doke et al 1994), the accumulation of H 2 O 2 (Doke et al 1994) and MDA (Smirnoff 1995, Xue et al 2010. The relative growth rate measurement, ion leakage and relative cell viability assay have been commonly used to distinguish heat-tolerant and heat-sensitive genotypes of many plant species (Kuo et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of HSP26 in transgenic Arabidopsis enhanced thermotolerance due to increased amount of free proline caused by the elevated proline biosynthetic pathway genes (Xue et al 2010). Transgenic rice plants with increased levels of sHSP17.7 protein exhibited significantly increased thermotolerance and UV-B tolerance compared to untransformed control plants (Murakami et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven transgenic plants with Imt1 were obtained, and transgenic plants of the T 2 generation were confirmed by β-glucuronidase (GUS) stain and PCR detection similarly as Xue et al (2010). We selected three transgenic lines (named N1, N2, and N3, corresponding to lanes 2, 3, and 4, respectively, in Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%